Factors associated with farmers’ use of indigenous and scientific climate forecasts in Rwenzori region, Western Uganda - Nbuka, Michael Robert; Chanda, Raban; Mmopelwa, Gagoitseope; Kato, Edward; Mangheni, Margaret Najjingo; Lesolle, David; Adedoyin, Akintayo; Mujuni, Godfrey (Springer, 2023)
Although scientific climate forecast (SF) distribution by national climate services has improved over time, farmers seem not to make good use of climate forecasts, a likely contributing factor to vulnerability to climate change. This study investigated factors associated with farmers’ use of SFs and indigenous forecasts (IFs) for agricultural use in the Rwenzori region, western Uganda. Household survey gathered data on demographic characteristics, climate information use and livelihood choices from 580 farmers. Data was analysed using the probit model. Results showed that significant factors associated with using both IFs and SFs were farm size, education, age, reception of scientific forecasts in local languages, agricultural extension access, short-mature crop access, farmer-to-farmer network and accessing forecasts through radio. This study shows that IFs were used complementarily with SFs. On the other hand, significant factors associated with using IFs only were livelihood choices such as tuber and goat production, access to government interventions on climate change adaptations, agro-ecological zone and social capital. Climate risks and climate risk perceptions negatively influenced the use of scientific forecasts. Co-production of climate information, capacity-building and active engagement of stakeholders in dissemination mechanisms can improve climate forecast use. Investments in more weather stations in various districts will therefore be a key factor in obtaining more accurate scientific forecasts and could lead to increased use of scientific climate forecasts. Governments in developing countries, the private sector, global and regional development partners should support investments in weather stations and capacity building of national meteorological systems.